THE PRELIMINARY STUDY OF RESPONSIVE WALL TECHNOLOGY FOR INDONESIA’S TRADITIONAL HOUSE; LEARNING FROM WOGO HOUSE, FLORES, INDONESIA - Agung Murti Nugroho (Journal of Architecture&ENVIRONMENT, 2011)
Indonesia’s traditional house have been imposed to steadily extend their functionality at comfortable living. The expanding application of basic in this context has lead to the emergence of the terms responsive technology to describe a building envelope form that can meet such demands, be it to a varying degree of success. Within the scope of this paper, intelligent behaviour for a building envelope by means of psychical process defined as adaptiveness or responsive to the environment which enables the envelope to solve conflicts and deal with new situations that occur in its interaction with the environment. This definition is used as a basis for an analysis of the functions a local technology can be expected to perform in the context of incident solar radiation and indoor temperature to the requirements of the traditional building occupant. Among the characteristics discussed in this paper, are the traditional wall’s ability to adapt the indoor climate and preferences, to choose the most appropriate response in each situation, to anticipate the development of environmental conditions, and to evaluate its own performance. Several stage are discussed: Wogo House’s responsive environment, wall technology, thermal environment and and contemporary context. The result of study in Flores Island illustrated that the traditional house achieved good thermal environment performance by responsive wall technology in Wogo traditional house.